Unveiling the Peril of Substandard and Falsified Medicines to Public Health and Safety in Africa: Need for All-Out War to End the Menace. Issue 1 (2017) - Aminu, Nafiu; Sha'aban, Abubakar; Abubakar, Abdulhakim; Gwarzo, Mahmud S.
The peril of substandard and falsified medicines (SFM) risk complete failure of the United Nations Sustainable Development Goals on access to safe, effective, quality, and affordable essential medicines in African countries. The global market volume of SFM could be up to US$200 billion, and up to 70% of the total medicines in circulation could be SFM in some parts of Africa. This dominance in the region is a clear sign of SFM proliferation, which continues to cause avoidable health hazards leading to severe adverse effects and devastating loss of human lives, by compromising treatment of chronic, infectious, and life-threatening diseases, such as malaria, cancer, pneumonia, tuberculosis, and diabetes. Besides these consequences to public health and safety, the economic and societal detriments are also grave. Although the recent advancement in detection technology coupled with increased collaborative efforts among some African drug regulatory agencies has led to a considerable success in countering the SFM pandemic, there is need to amplify and intensify such efforts in order to curb or totally eradicate the menace. Here, we provide an overview of the detrimental impact of SFM on the healthcare system in African countries and highlight various strategies for curbing the menace in order to arrest its hazardous consequence to the public.